1974
DOI: 10.1111/j.1751-1097.1974.tb06571.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photolysis of 3‐methyllumiflavin

Abstract: Abstract—The pH dependence of the transient absorptions of 3‐methyllumiflavin has been investigated with laser photolysis in the nanosecond time range. Three different transient species (I, II and III) can be observed. The analysis of the decay curves shows that I and II can be ascribed to the optical absorption spectra of the lowest excited singlet and triplet states, respectively. Their appearance is not affected by a change of pH of the solution. The transient spectra due to species III have a decay which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Ultrafast process of the formation of the C T complex between excited flavin and tryptophan takes place within 33 ps and the produced C T state decays in a few ns. It should be noted that the present work shows no indication of the production of long-lived species such as free radical of flavins (Massey and Palmer, 1966) or flavin triplet state (Visser et al, 1974) which shows absorption spectra in the 45G800-nm region. The formation of the CT complex in the relatively nonpolar environment of protein should be possible only when the isoalloxazine ring of FMN or Trp-60 possess motional freedom in picosecond time-scale.…”
Section: Resultscontrasting
confidence: 69%
“…Ultrafast process of the formation of the C T complex between excited flavin and tryptophan takes place within 33 ps and the produced C T state decays in a few ns. It should be noted that the present work shows no indication of the production of long-lived species such as free radical of flavins (Massey and Palmer, 1966) or flavin triplet state (Visser et al, 1974) which shows absorption spectra in the 45G800-nm region. The formation of the CT complex in the relatively nonpolar environment of protein should be possible only when the isoalloxazine ring of FMN or Trp-60 possess motional freedom in picosecond time-scale.…”
Section: Resultscontrasting
confidence: 69%
“…Meanwhile, only several authors performed relevant studies: Müller et al (1973) observed the temperature changes in absorption spectra due to flavins (and flavins derivatives) dimers. The existence of flavins dimers has also been proposed by Harders et al (1974), Visser et al ( 1974 and Heelis et al (1978). Song et al (1972) based on the phosphorescence excitation spectra at T=77 K suggested extremely weak fluorescence of riboflavin (and its derivative) dimer.…”
Section: Investigations Of Flavins Dimerization Flavins Dimers In Phmentioning
confidence: 94%
“…Until the eighties, the dimerization process of FMN and its influence on absorption spectra has not been studied, although the suggestions that flavins might form dimers had appeared earlier in literature [50,51,65]. Song et al [57] suggested extremely weak fluorescence of riboflavin (and its derivative) dimer based on the phosphorescence excitation spectra at T = 77 K. The mentioned studies have not been, however, oriented towards the determination of dimerization constant and investigation of dimerization process.…”
Section: Introductionmentioning
confidence: 98%
“…In water, the solubility of FMN reaches 8 × 10 −2 M, but in investigations of FMN in water the following range of concentrations was used: from C = 1 × 10 −5 M to 1.8 × 10 −2 M (in publications [62,64,35,68]). However, the solubility of FMN in the glycerol-water (GW) solution and in PVA is higher, so C max = [ [50][51][52] 9 × 10 −2 M was used for GW solution [64,69,70] and C max = 1 M for PVA [61,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation